Clinical safety of the ProMRI implantable cardioverter-defibrillator systems during head and lower lumbar magnetic resonance imaging at 3 T: results of the ProMRI 3T ENHANCED Master study. Issue 11 (19th July 2019) - Zbinden, Rainer; Wollmann, Christian; Brachmann, Johannes; Michaelsen, Jochen; Steinwender, Clemens; Kovoor, Pramesh; Kelle, Sebastian; McGavigan, Andrew D; Ching, Chi Keong; Figtree, Gemma A; Schmidt, Jan; Timmel, Tobias; et al.
Abstract: Aims: There have been no published studies on the safety of magnetic resonance imaging (MRI) at 3 Tesla (3 T) in patients with MRI-conditional implantable cardioverter-defibrillators (ICDs). The aim of this study was to assess clinical safety of the Biotronik ProMRI ICD system during non-diagnostic head and lower lumbar scans under 3 T MRI conditions. Methods and results: The study enrolled 129 patients at 12 sites in Australia, Singapore, and Europe. Predefined head and lower lumbar MR scans (total duration ≈30 min) were performed in 112 patients. Three primary endpoints were evaluated from the pre-MRI to the 1-month post-MRI visit: (i) freedom from serious adverse device effects (SADEs) related to MRI (hypothesized to be >90%); (ii) pacing threshold invariance for all leads (geometric mean of the patient-wise ratios for 1 month vs. pre-MRI was hypothesized to be <1.07); and (iii) sensing amplitude invariance (geometric mean of the ratios was hypothesized to be >0.993). No MRI-related SADE occurred (SADE-free rate 100%, 95% confidence interval 95.98–100%). Pacing threshold and sensing amplitudes fulfilled the invariance hypotheses with high statistical significance ( P  < 0.0013). No threshold increase >0.5 V or sensing amplitude decrease by >50% was observed (secondary endpoints). Lead impedances, battery capacity, and detection and treatment of arrhythmias by ICDs were not affected by MRI scans. Conclusion: The head and lower lumbar scans under specific 3 T MRI conditions were safe in the investigated MR-conditional ICD systems. There was no evidence of harm to the patients or any negative influence of the MRI scan on the implanted systems.